Systematic Mapping Study: Peran Women Entrepreneurship dalam Networking pada UMKM Pariwisata - Raja Ainaya Alfatiha; Margo Purnomo; Ratih Purbasari (Program Studi Manajemen Fakultas Ekonomi UMRAH, 2022)
Research on women entrepreneurship has attracted a lot of interest from researchers, besides that, the use of networking and the tourism industry sector is also always associated with women entrepreneurship. So this study aims to map the topics of women entrepreneurship, networking and tourism using the Systematic Mapping Study (SMS) method to help see the development of research. The data search was carried out by using the Scopus database with the final result of 23 articles. Based on the mapping results, it is shown that the most widely used research method for the topic of women entrepreneurship is qualitative, namely 12 (52.17%) articles. The least research focus is development strategy and innovation, so this focus can be a reference for further research. The dominant paper type used is the evaluation research category, which is 12 (52.17%) articles. Furthermore, the publication trend of countries that do a lot of research on this topic is the UK and South Africa, namely 5 (21.74%) articles and the trend of publication from year to year peaks in 2020 with 7 (30.4%) articles. Based on the mapping results, there are still gaps in the topic of this research, so there are still opportunities to produce updates